Carotenoids are more bioavailable from papaya than from tomato and carrot in humans: a randomised cross-over study. Issue 3 (12th August 2013) - Schweiggert, Ralf M.; Kopec, Rachel E.; Villalobos-Gutierrez, Maria G.; Högel, Josef; Quesada, Silvia; Esquivel, Patricia; Schwartz, Steven J.; Carle, Reinhold
Abstract : Carrot, tomato and papaya represent important dietary sources of β-carotene and lycopene. The main objective of the present study was to compare the bioavailability of carotenoids from these food sources in healthy human subjects. A total of sixteen participants were recruited for a randomised cross-over study. Test meals containing raw carrots, tomatoes and papayas were adjusted to deliver an equal amount of β-carotene and lycopene. For the evaluation of bioavailability, TAG-rich lipoprotein (TRL) fractions containing newly absorbed carotenoids were analysed over 9·5 h after test meal consumption. The bioavailability of β-carotene from papayas was approximately three times higher than that from carrots and tomatoes, whereas differences in the bioavailability of β-carotene from carrots and tomatoes were insignificant. Retinyl esters appeared in the TRL fractions at a significantly higher concentration after the consumption of the papaya test meal. Similarly, lycopene was approximately 2·6 times more bioavailable from papayas than from tomatoes. Furthermore, the bioavailability of β-cryptoxanthin from papayas was shown to be 2·9 and 2·3 times higher than that of the other papaya carotenoids β-carotene and lycopene, respectively. The morphology of chromoplasts and the physical deposition form of carotenoids were hypothesised to play a major role in the differences observed in the bioavailability of carotenoids from the foods investigated. Particularly, the liquid-crystalline deposition of β-carotene and the storage of lycopene in very small crystalloids in papayas were found to be associated with their high bioavailability. In conclusion, papaya was shown to provide highly bioavailable β-carotene, β-cryptoxanthin and lycopene and may represent a readily available dietary source of provitamin A for reducing the incidence of vitamin A deficiencies in many subtropical and tropical developing countries.